Features of the adaptive response to the short-term influence of microwave radiation in Drosophіla melanogaster stocks with black mutation - Горенська, О. В.; Шкорбатов, Ю. Г.; Гаврилов, А. Б. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The influence of extremely high frequency (EHF) radiation with wave frequency 37.7 GHz, power density 10 µW and 100 µW on formation of Drosophila melanogaster some important adaptive traits has been studied. We used wild type stock Canton-S, black and blackCanton-S mutant stocks. It has been shown that short-term exposure of Drosophila eggs to the microwave radiation increases the duration of preimaginal stage and reduces the resistance of adults to starvation. The part of larvae died at the pupal stage do not significantly differ from the control level in all experimental variants. The preimaginal development rate depends largely on external influence (h2♀=13,86%, h2♂=18,48%). The main factor determining the lifespan of flies under starvation after the action of microwaves is genotype (h2♀=43,42%, h2♂=59,52%).